CO concentration forecasting with attention-based LSTM and EMD for urban areas in Selangor - Zaini N.; Ean L.W.; Ahmed A.N.; Chow M.F.; Malek M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Air quality; Carbon monoxide; Deterioration; Forecasting; Health risks; Long short-term memory; Air pollutants; Air quality levels; Ambient air; Carbon monoxide concentration; Deep learning; Empirical Mode Decomposition; Forecasting and air quality; Heart disease; Human health; Urban areas; Empirical mode decomposition